PENERAPAN ASAS TRIKON DALAM PEMBELAJARAN DI SEKOLAH DASAR - Kadek Jayanthi Riva Prathiwi; I Komang Wisnu Budi Wijaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to analyze the application of Trikon principles in learning in elementary schools. This research is included in literature study research. The data source in this research is in the form of literature related to the Trikon concept, which is actually the result of Ki Hadjar Dewantara's thoughts. Data collection techniques consist of collecting literature, reviewing and selecting literature, analyzing and synthesizing, and ending with drawing conclusions. The data analysis technique uses content analysis techniques. The results of the research state that the Trikon principle can be applied in learning in elementary schools by implementing student-centered learning, applying the open ended approach, contextual approach and differentiated learning.